REAKTUALISASI KONSEP ANAK SEBAGAI MUSUH DALAM AL-QUR’AN (STUDI ATAS QS. AT-TAGHABUN: 14) - Rohmatuzzahrok, Nila; Susanti, Rini (Yayasan Baitul Hikmah al-Zain, 2024)
This article discusses the meaning of QS. at-Taghabun: 14 when compared to actual issues in Indonesia. The verses that came down in response to actual situations or issues in 7th century Arab society then came into contact with various social dynamics, cultures and traditions. Specifically, this article will explore the concept of children as enemies in the QS. at-Taghabun: 14 which is actualized in the current context in Indonesia. This paper is a type of analytical descriptive that focuses on qualitative data using the ma'na cum maghzā approach. The use of ma'na cum maghzā is expected to be able to provide a bridge to arrive at a representative meaning. The important findings in this paper consist of three important things. First, children are essentially enemies, which means children can indeed become enemies of their parents. As in cases of murder committed by children against their parents. Second, majazi enemies, namely enemies which refer to a child's actions that can prevent their parents from worshiping Allah or even a child's actions that can lead their parents to things that are prohibited by Allah. The maghzā contained in this verse is broadly based on three principles. First, the priority of enforcing and implementing Islamic Sharia. Second, be proportional and alert to ownership. Third, pay attention to the values ​​of ihsan in carrying out obligations